Crystal structure of ethyl 2-cyano-3-[(1-ethoxyethylidene)amino]-5-(3-methoxyphenyl)-7-methyl-5H-1,3-thiazolo[3,2-a]pyrimidine-6-carboxylate - M. S. Krishnamurthy; Noor Shahina Begum (Acta Crystallographica Section E: Crystallographic Communications, 2015)
In the title compound, C22H24N4O4S, the central pyrimidine ring adopts a sofa conformation with the ring-junction N atom displaced by 0.2358 (6) Å from the mean plane of the remaining ring atoms. The 3-methoxyphenyl ring, at the chiral C atom opposite the other N atom, is positioned axially and is inclined to the thiazolopyrimidine ring with a dihedral angle of 83.88 (7)°. The thiazole ring is essentially planar (r.m.s. deviation = 0.0034 Å). In the crystal, pairs of weak C—H...O hydrogen bonds link molecules related by twofold rotation axes to form R22(8) rings, which in turn are linked by weak C—H...N interactions, forming ribbons along [-110]. In addition, π–π stacking interactions [centroid—centroid distance = 3.5744 (15) Å] connect the ribbons, forming slabs lying parallel to (001).